2021
DOI: 10.3390/diagnostics11071250
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Expression of MTUS1 Is Associated with Poor Survival in Patients with Lung Adenocarcinoma

Abstract: Microtubule-associated tumor suppressor 1 (MTUS1) is thought to be downregulated in arious human cancers, which suggests its role as a tumor suppressor. This study investigated the clinicopathological significance of MTUS1 expression in lung adenocarcinoma. Tissue microarray blocks consisting of 161 cases were constructed, and immunohistochemical staining was used to assess MTUS1 expression. Correlations of MTUS1 expression and clinicopathological parameters were analyzed. In addition, we used public databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…To determine if coal dust can cause lung cell proliferation, we used Ki67 as an indicator of proliferation ( Jee et al, 2021 ). The cell proliferation was significantly higher in the CWP-3M group than in the CWP-1M and NS groups.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if coal dust can cause lung cell proliferation, we used Ki67 as an indicator of proliferation ( Jee et al, 2021 ). The cell proliferation was significantly higher in the CWP-3M group than in the CWP-1M and NS groups.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that recombinant overexpression of MTUS1 inhibited tumor cell proliferation, while reduced MTUS1 expression was associated with increased cell proliferation of oral squamous cell carcinoma cells, breast cancer cells, and ovarian cancer cells [ 9 ]. Reduced MTUS1 expression is also associated with poor prognosis in lung adenocarcinoma [ 11 ], gallbladder adenocarcinoma [ 12 ], renal cell carcinoma [ 13 ], bladder carcinoma [ 14 , 15 ], adenoid cystic carcinoma of the salivary gland [ 16 ], and squamous cell carcinoma of the tongue [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MTUS1 gene has transcript variants of various isoforms through alternative splicing that encode mitochondrial protein with tumor suppressor activity [ 7 , 8 ]. MTUS1 is downregulated in several types of cancers, including colorectal carcinoma [ 9 , 10 ], lung adenocarcinoma [ 11 ], gallbladder adenocarcinoma [ 12 ], renal cell carcinoma [ 13 ], bladder carcinoma [ 14 , 15 ], adenoid cystic carcinoma of salivary gland [ 16 ], squamous cell carcinoma of the tongue [ 17 ], head and neck squamous cell carcinoma [ 18 ], uveal melanoma [ 19 ], and breast carcinoma [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Logistic regression showed that the expression of MTUS1 in CRC was associated with advanced pathological stages and N stages, suggesting that MTUS1 is important for tumour invasion and lymph node MTUS1 can also regulate cell division by disturbing the microtubule cytoskeleton and can also be used to predict the treatment response to paclitaxel-based chemotherapy in breast cancer [21][22][23]. In lung adenocarcinoma tissues, low MTUS1 expression is related to various clinical-pathological parameters, such as tumour size, Ki-67 proliferation index, lymphovascular invasion, and lymph node metastasis, which lead to the correspondingly poor prognosis of patients [14]. Moreover, MTUS1 expression levels can be synergistically inhibited by miR-19a and miR-19b, thereby contributing to lung cancer cell proliferation and migration [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested that MTUSI is downregulated in multiple cancers, including CRC. MTUS1 is also associated with poor prognosis in patients with lung adenocarcinoma, gastric cancer, renal cell carcinoma, gallbladder carcinoma, salivary adenoid cystic carcinoma, and oral tongue squamous cell carcinoma [10,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%